2020
DOI: 10.7759/cureus.10466
|View full text |Cite
|
Sign up to set email alerts
|

Returning to Sport After Anterior Cruciate Ligament Reconstruction in Physically Active Individuals

Abstract: Background Physically active individuals are susceptible to sports injuries, one of which is anterior cruciate ligament (ACL) injury. ACL injury can be managed conservatively or by surgical reconstruction. Returning to sport (RTS) after ACL injury is one of the main goals of ACL reconstruction (ACLR). However, rates of return vary and can be affected by several factors. The objectives of this study were to estimate the rate of return and to identify the factors that might affect RTS after ACLR. Methods This wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
(58 reference statements)
1
8
0
Order By: Relevance
“…Every patient must be evaluated frequently and return gradually to his previous activities. A recent cross-sectional study demonstrated a low rate of returning to sports after ACL reconstruction, with psychological aspects playing a significant role and fear of reinjury being the most frequent cause of not returning to sport [ 6 ]. A systematic review and meta-analysis by Ardern et al [ 30 ] showed that on average, 81% of people returned to any sport, 65% returned to their pre-injury level of sport and 55% returned to the competitive level sport after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Every patient must be evaluated frequently and return gradually to his previous activities. A recent cross-sectional study demonstrated a low rate of returning to sports after ACL reconstruction, with psychological aspects playing a significant role and fear of reinjury being the most frequent cause of not returning to sport [ 6 ]. A systematic review and meta-analysis by Ardern et al [ 30 ] showed that on average, 81% of people returned to any sport, 65% returned to their pre-injury level of sport and 55% returned to the competitive level sport after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The primary goal of surgery is to achieve a functionally stable knee while minimizing morbidity and complications associated with the procedure. The autograft of bone-patella tendon-bone (BPTB) and the autograft of four-strand hamstring tendon, are the most commonly used ones on ACL reconstruction around the world [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Following ACLR, the goal of surgery and rehabilitation is to return the patient to their preinjury functional levels [14][15]. To evaluate the effectiveness of surgical and rehabilitation outcomes, tools capable of assessing patient reported outcome in a reliable and valid fashion are necessary [16][17][18].…”
Section: Mean ± Sd Rangementioning
confidence: 99%
“…Meanwhile, physical conditions such as persistent knee symptoms such as pain, swelling, stiffness, instability, and weakness also cause individuals not to return to their sport. 25 Based on the data collection and analysis results, there were indications of variability in the participants' postreconstruction duration. The average post-ACL reconstruction duration was 10.9 ± 5.9 months with a variance of 35.2, a maximum of 24 months, and a minimum of 3 months, so the range was 21 months.…”
Section: Original Articlementioning
confidence: 99%
“…Knee physical function can affect the psychological response, so if the individual has stable and good knee function, the psychological response experienced is also the same and vice versa. 25,26 This can cause a strong correlation of the ACL-RSI score with each subscale KOOS.…”
Section: Original Articlementioning
confidence: 99%